Comparative transcriptomic and metabolomics analysis of ovary in Nilaparvata lugens after trehalase inhibition - Yongkang Liu; Fan Yang; Sijing Wan; Xianzhong Wang; Liwen Guan; Yan Li; Caidi Xu; Binghua Xie; Shigui Wang; Xiao-Ling Tan; Bin Tang (BMC Genomics)
Abstract The fecundity of Nilaparvata lugens (brown planthopper) is influenced by trehalase (TRE). To investigate the mechanism by which trehalose affects the reproduction of N. lugens, we conducted a comparative transcriptomic and metabolomic analysis of the ovaries of N. lugens following injection with dsTREs and validamycin (a TRE inhibitor). The results revealed that 844 differentially expressed genes (DEGs) were identified between the dsGFP and dsTREs injection groups, with 317 up-regulated genes and 527 down-regulated genes. Additionally, 1451 DEGs were identified between the water and validamycin injection groups, with 637 up-regulated genes and 814 down-regulated genes. The total number of DEGs identified between the two comparison groups was 236. The overlapping DEGs were implicated in various biological processes, including protein metabolism, fatty acid metabolism, AMPK signaling, mTOR signaling, insulin/insulin-like growth factor signaling (IIS), the tricarboxylic acid (TCA) cycle, oxidative phosphorylation, and the cellular process of meiosis in oocytes. These results suggest that the inhibition of TRE expression may lead to alterations in ovarian nutrient and energy metabolism by modulating glucose transport and affecting amino acid metabolic pathways. These alterations may influence the reproduction of N. lugens by modulating reproductive regulatory signals. These findings provide robust evidence supporting the mechanism through which trehalase inhibition reduces the reproductive capacity of N. lugens.